Left dorso-lateral repetitive transcranial magnetic stimulation affects cortical excitability and functional connectivity, but does not impair cognition in major depression. - Shajahan, P; Glabus, M; Steele, J; Doris, AB; Anderson, K; Jenkins, J; Gooding, P; Ebmeier, K (2002)
PURPOSE: Transcranial magnetic stimulation (TMS) has been used for over a decade to investigate cortical function. More recently, it has been employed to treat conditions such as major depression. This study was designed to explore the effects of differential treatment parameters, such as stimulation frequency. In addition, the data were examined to determine whether a change in connectivity occurred following TMS. METHOD: Fifteen patients with major depression were entered into a combined imaging and treatment experiment with single photon emission computed tomography (SPECT) and repetitive transcranial magnetic stimulation (rTMS) over left dorso-lateral prefrontal cortex (DLPFC). Brain perfusion during a verbal fluency task was compared between pre- and poststimulation conditions. Patients were then treated with 80% of motor threshold for a total of 10 days, using 5000 stimuli at 5, 10 or 20 Hz. Tests of cortical excitability and neuropsychological tests were done throughout the trial. FINDINGS: Patients generally improved with treatment. There was no perceptible difference between stimulation frequencies, which may have reflected low study power. An increase in rostral anterior cingulate activation after the treatment day was associated with increased functional connectivity in the dorso-lateral frontal loop on the left and the limbic loop on both sides. No noticeable deterioration in neuropsychological function was observed. CONCLUSION: TMS at the stimulation frequencies used seems to be safe over a course of 5000 stimuli. It appears to have an activating effect in anterior limbic structures and increase functional connectivity in the neuroanatomical networks under the stimulation coil within an hour of stimulation.